Strategi Peningkatan Pendapatan Petani Kelapa Sawit Umur Tanaman 21-25 Tahun Di Kecamatan Dolok Masihul - Darma, Endra; Iskandarini; Siahaan, Elisabet (Universitas Medan Area, 2024)
The income of farmers who have plants aged 21-25 years based on productivity trends will experience a decline. The decline that occurs will be directly proportional to crop productivity so that the average decline in income for farmers aged 21-25 years is 1-5% per year. The average decline that has occurred is 19.11% since 2021. This research aims to increase the income of oil palm farmers aged 21-25 years in Dolok Masihul so that the decline in income experienced by farmers returns to normal conditions, namely 1-5%. The population of this research is all oil palm farmers in Dolok Masihul. Sampling was carried out using the probability sampling method and the samples were 125 farmers whose plants were 21-25 years old. The research was conducted using qualitative and quantitative methods using SWOT and QSPM analysis. The results of this research provide a defensive strategy for increasing income from plants aged 21-25 years in the short term, namely 1 to 3 years. Farmers can make improvements through crop management based on intensity and rainy days, controlling rat pests using natural enemies and using rodenticides. Fertilizer management and storage based on fertilizer properties. In the long term, namely in the next 3 to 8 years, income can be increased through the formation of farmer groups with legal entities in an effort to obtain fertilizer subsidies, counseling, procurement of shunting equipment in hilly areas and efforts to obtain CSR (Corporate Social Responsibility) funds.